Experiences and perceptions of emergency department nurses regarding people who present with mental health issues: a systematic review protocol. (September 2019) - Quirke, Mary B.; Donohue, Grainne; Prizeman, Geraldine; White, Patricia; McCann, Edward
ABSTRACT: Objective: The objective of this review is to identify, appraise and synthesize available evidence related to the experiences and perceptions of emergency department (ED) nurses regarding people with any mental health issue who present at the ED. Introduction: The ED is often the first point of contact for patients with a mental health issue, due to a shortage of available mental health services. Nursing staff in the ED are involved in key clinical decision making and hands-on care for these patients, despite a lack of mental health specialist training. In order to improve patient outcomes in the ED setting, it is necessary to have a thorough understanding of how ED nurses' experiences with this population affect their clinical decision making. Inclusion criteria: This review will consider studies that include ED nurses, with or without mental health specialist training, working in urban and rural EDs in healthcare settings worldwide. Qualitative studies that explore the experiences and perceptions of ED nurses regarding people who present with mental health issues in the ED setting will be considered. Studies published in English will be considered, with no date limitations. Methods: CINAHL complete, MEDLINE, PsycINFO, Embase, Scopus, Web of Science and Google Scholar will be searched, along with several sources of gray literature. Retrieval of full-text studies, assessment of methodological quality and data extraction will be performed independently by two reviewers. Findings will be pooled using meta-aggregation, and a ConQual Summary of Findings will be presented.